2015
DOI: 10.1371/journal.pone.0130096
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Maxillary Protraction with or without Rapid Maxillary Expansion and Age Factors in Treating Class III Malocclusion: A Meta-Analysis

Abstract: We conducted a comprehensive meta-analysis of 12 studies to examine whether maxillary protraction face mask associated with rapid maxillary expansion (FM/RME) could be an effective treatment for Class III malocclusion and to evaluate the effect of timing on treatment response. Patients with a maxillary deficiency who were treated with FM with or without RME were compared with those who had an untreated Class III malocclusion. In both treatment groups, forward displacement of the maxilla and skeletal changes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
42
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 66 publications
8
42
0
6
Order By: Relevance
“…Class III orthopaedic therapy includes several appliances, not always assessed by RCTs . Other systematic reviews comprised randomised and non‐randomised studies without evaluating if the study design could affect the results . Indeed, an interesting finding of this review was that some results may be overestimated due to the study design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Class III orthopaedic therapy includes several appliances, not always assessed by RCTs . Other systematic reviews comprised randomised and non‐randomised studies without evaluating if the study design could affect the results . Indeed, an interesting finding of this review was that some results may be overestimated due to the study design.…”
Section: Discussionmentioning
confidence: 99%
“…Six systematic reviews and meta‐analysis have recently been published on skeletal Class III malocclusion treatment , only focusing on RCTs or a single appliance.…”
Section: Introductionmentioning
confidence: 99%
“…The skeletal Class III relationship is produced by alterations in size or position of the maxilla and jaw, presenting as retrusion or hypoplasia of the maxilla in the presence of normal jaw, as prognathism or macrognathism with normal maxilla, or as an alteration of the position and size of both jaws, involving sagittal, transversal, and vertical disharmonies (Toffol, Pavoni, Baccetti, Franchi, & Cozza, ; Zhang, Qu, Yu, & Zhang, ). Incidence of Class III malocclusion varies among populations, ranging from 1% to 5% in Whites, 5% in Latinos, and from 9% to 19% in Asians (Haynes, ; Thilander, ; Toffol et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Wolfe et al reported that, compared with a Class I control group, patients with Class III malocclusion display hyperdivergent jaws and increased inferior facial height (Wolfe, Araujo, Behrents, & Buschang, ). Treatment has been aimed at maxillary advancement and/or control of jaw growth, and several devices have been designed for this purpose such as protraction face masks (FMs), chincups, mandibular cervical hedgear, and functional orthopedic appliances (Baccetti, Rey, Angel, Oberti, & McNamara, ; Baccetti, Rey, Oberti, Stahl, & McNamara, ; Baik, Jee, Lee, & Oh, ; Rey, Angel, Oberti, & Baccetti, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation